Impact of cricket protein powder replacement on wheat protein composition, dough rheology and bread quality - Perez-Fajardo, Mayra Angelina (Kansas State University, 2020)
The continuous rise in population, environmental concerns, and an increasing shift of consumers’ belief towards eating sustainable foods has led researchers to look for alternate sources of protein. Insect proteins are novel protein sources that are environmentally friendly due to their lower greenhouse gas emissions when compared to beef, poultry, and pork. Farming insects requires less resources compared to raising livestock. Insects are high in protein, contain chitin which is a source of fiber, and are a good source of B vitamins. There is a wide variation in nutritional and functional quality of protein depending on the type of insect. The objective of this project was to understand how cricket protein powder affects the mixing, pasting and dough development characteristics of bread dough. Two different cricket protein powders, GrioPro (G) and Entomo Farms (E), were tested at replacement levels of 10 and 20% (of total flour weight). Protein powders were first characterized for their functional properties. Dough samples collected at peak torque development were subjected to size exclusion-HPLC analysis to quantify the change in soluble polymeric proteins (SPP) and insoluble polymeric proteins (IPP). MixoLab constant and optimized water absorption protocols were used to study the effect of cricket protein powder replacement on dough development. Dough extensibility was tested using the Kieffer Rig protocol. Breads were baked with 5, 10, or 20% replacement levels of cricket protein powder. Loaf volume, and color were measured, and bread slices underwent C-Cell analysis and texture profile analysis (TPA) at 0, 1, 3 and 7 days. In general, incorporation of powders G and E led to two opposite effects. Dough samples with powder E showed lower peak areas (9,432 and 17,346 mAu) of IPP compared to the control (23360 mAu) while the SPP dough samples showed higher peak areas (41,414 and 44,133 mAu) to the control (41,212 mAu). Use of powder G led to an increased stability, significantly higher C1 torque (20% level), and an increase water absorption. Replacement of wheat flour with powder E led to softer doughs with a decreased stability at the 20% replacement level and no significant difference in water absorption. Peak viscosities were significantly decreased for all replacement levels of both G and E powders. Extensibility was significantly decreased as the replacement level increased for all treatments. Loaf volume also decreased as the replacement level increased for all treatments. Color results showed a significant decrease in L-value and a significant increase in a, and b-values thus producing a crumb color like that of whole wheat breads. Powder G at 10 and 20% replacement levels significantly decreased the area occupied by air cells, the average air cell diameter, and cell wall thickness. Both powder E and G led to a decreased amount of number of air cells. TPA results showed a significant increase in hardness at higher replacement levels with G being harder than E. Chewiness also increased as the replacement level increased while cohesiveness, springiness, and resilience decreased as the replacement levels increased for either G or E.
Keywords: Cricket protein powder; Molecular weight distribution; Cricket protein functionality; Dough rheology; Test baking; Texture Profile Analysis